The Impact of Field Court Attendance Notices on Property Crime in New South Wales, Australia - Manning, Matthew (Journal of quantitative criminology, 2018)
This paper investigates the impact of Field Court Attendance Notices (FCANs) on rates of property crime in New South Wales (NSW), Australia. FCANs are used for relatively minor offenses, are issued ‘on the spot', and provide an alternative to the time consuming process of arresting an alleged offender and taking them to the police station for processing. Despite their use in NSW for over 20 years, this study is the first to evaluate their impact on crime.